Analysis The Role of Principle as Supervisor in The Implementation of School-Based Management - Arifin, Arifin; Mamonto, Tofhan; Assery, Syeh; Lahiya , Arkam; Ramli , Akhmad (Mudir : Jurnal Manajemen Pendidikan, 2023)
The principal's function as a supervisor in the implementation of school-based management is covered in this paper. The goal of this research is to characterize the principal's position as a supervisor based on four components of school-based management, including creating and evaluating school programs, managing the learning process, handling personnel issues, and managing relationships with the committee. One of school served as the research site. Descriptive qualitative methodology is the research technique employed. The school committee chairman, instructors, and the principal were the sources of the data. The findings indicated that the principal's position as a supervisor in overseeing the educational process and school-community interactions was ideal. However, it has not been functioning at its best in its capacity as a supervisor in developing and assessing school programs and managing staff. Suggestions in this situation include the principal setting a good example of teacher discipline. It is important to retain the role that parents or committees play in raising learning standards, and it is hoped that more observations will be made to see if the principal's supervising efforts have a reciprocal effect.